1995
DOI: 10.3109/14756369509042811
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T Lymphocyte Actnation by a Novel p56lckTyrosine Kinase Inhibitor

Abstract: A new p56lck tyrosine kinase inhibitor WIN 61651 [1,4-dihydro-7-(4-methyl-1-piperizinyl)-1-(4-(4-methyl-1-piperi zinyl))phenyl- 4-oxo-3-quinolinecarboxamide) is described. WIN 61651, which is competitive with ATP, demonstrates selectivity for the lymphoid restricted tyrosine kinase p56lck over serine/threonine kinases, such as protein kinase C and protein kinase A, and over some other tyrosine kinases, including erbB2, epidermal growth factor receptor, and insulin receptor; however, it is equipotent for inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Other investigators have similarly reported that staurosporine is a potent inhibitor of Src family kinases (IC 50 ϭ 90 -200 nM) and was also effective for inhibition of nonreceptor tyrosine and serine/threonine protein kinases (36,37). A new quinolone derivative, WIN 61651, has also been described as an inhibitor of p56 lck (46). This compound is significantly less potent than PP1 for inhibition of Lck (18 -24 M) and appears to be less selective since it demonstrates equal potency for the platelet-derived growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have similarly reported that staurosporine is a potent inhibitor of Src family kinases (IC 50 ϭ 90 -200 nM) and was also effective for inhibition of nonreceptor tyrosine and serine/threonine protein kinases (36,37). A new quinolone derivative, WIN 61651, has also been described as an inhibitor of p56 lck (46). This compound is significantly less potent than PP1 for inhibition of Lck (18 -24 M) and appears to be less selective since it demonstrates equal potency for the platelet-derived growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, damnacanthal displayed more than 100-fold selectivity for p56 lck over serine/threonine kinases, PKA, and PKC, and more than 40-fold selectivity over four receptor tyrosine kinases (EGF, PDGF, Erb2 and Ins). It also demonstrated modest (7 to 20-fold) selectivity for p56 lck over the homologous enzymes p60 src and p59 fyn [152]. The study of mechanism of action demonstrated that damnacanthal was competitive with the peptide-binding site, but mixed non-competitive with the ATP site.…”
Section: Iv73 Damnacanthalmentioning
confidence: 95%
“…These compounds were shown to be more potent than first generation inhibitors such as Genistein and WIN61651 (Akiyama et al, 1987;Faltynek , 1995). In addition, they also improved upon second generation inhibitors, such as pyrazolopyrimidines (PP1 and PP2) (Hanke et al, 1996), which until now were the most potent and specific inhibitors of the Src kinase family of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibitors of Lck currently exist (Faltynek et al, 1995;Hanke et al, 1996;Gimsa et al, 1999;Trevillyan et al, 1999), they are limited in both their potency and selectivity for Lck over other tyrosine kinase enzymes. In this study, we show that a novel series of Src kinase inhibitors (Celltech Src kinase inhibitors or CT-SKI) are more potent and selective for Src kinase enzymes than previous inhibitors, such as PP1 (Hanke et al, 1996).…”
mentioning
confidence: 99%